The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.2196/24907
|View full text |Cite
|
Sign up to set email alerts
|

Effective German and English Language mHealth Apps for Self-management of Bronchial Asthma in Children and Adolescents: Comparison Study

Abstract: Background Mobile health (mHealth) apps hold great potential for asthma self-management. Data on the suitability of asthma apps intended for children are insufficient, and the availability of German language apps is still inadequate compared with English language apps. Objective This study aims to identify functional asthma apps for children in German and to compare them with English language apps. In line with the PRISMA (Preferred Reporting Items for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
21

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(60 citation statements)
references
References 37 publications
0
36
0
21
Order By: Relevance
“…The properties of the included studies are summarized in Table 1. Of these, 9 studies were original research studies,9,23–30 one was a conference paper,31 and one was a comparison study 32…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of the included studies are summarized in Table 1. Of these, 9 studies were original research studies,9,23–30 one was a conference paper,31 and one was a comparison study 32…”
Section: Resultsmentioning
confidence: 99%
“…Protection should be provided for personal data, and integration of person-generated health data via mHealth solutions needs to be done in a way that safeguards the privacy and integrity of individuals. 32 Therefore, a secure Web app specifically designed to support data capture for research studies can be used to ensure the security and privacy of person-generated health data. 30 Furthermore, a conceptual model is proposed to describe how person-controlled real-world data can be shared effectively with the chronic care management team in a way that supports individual health, while respecting personal data privacy and control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was questioned if such apps were effective in asthma care since there are no official criteria on its evaluation, lack of FDA regulation, and their lack of effectiveness in monitoring childhood asthma. Furthermore, they are usually created without guidance from medical experts [ 13 18 ]. However, mobile apps continue to be used in various aspects of asthma care to remotely monitor patients and in the self-monitoring of patients’ asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This can help to decipher if the patients are taking acceptable breaths with their medications [ 33 ]. Other popular apps being used include Kiss my asthma (KmAsthma), Asthma MD, AsthmaXcel, Asthma Australia, Ask Me, AsthMe!, and MASK-air [ 18 , 34 , 35 ]. Two recent reviews looking at various digital technologies showed that it can be implemented in asthma care.…”
Section: Introductionmentioning
confidence: 99%